INNOVATIVE APPROACHES IN ARCHITECTURAL EDUCATION: INTEGRATING SUSTAINABILITY AND GREEN DESIGN PRINCIPLES IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Architectural education in Nigeria faces the challenge of aligning with global sustainability imperatives while addressing local socio-environmental contexts. This study explores innovative pedagogical approaches to integrating sustainability and green design principles within architectural education in Cross River State, Nigeria. Utilizing a mixed-methods approach, primary data were collected through questionnaires and semi-structured interviews with 150 participants, including students, educators, and practicing architects. The findings reveal a high awareness of sustainability (78.6%) but limited practical application due to outdated curricula, insufficient faculty training, and resource constraints. Innovative strategies, such as experiential learning, community-led design studios, and integration of African architectural traditions, were identified as effective in fostering sustainable design thinking. Demographic analysis indicates a youthful participant pool (68% aged 18–30), with a gender distribution of 62% male and 38% female, reflecting the region’s educational trends. The study proposes a framework for curriculum reform, emphasizing interdisciplinary collaboration, digital tools like Building Information Modeling (BIM), and context-driven sustainability studios. These findings contribute to the discourse on sustainable architectural pedagogy in developing nations, offering actionable recommendations for educators and policymakers.